Finerenone Attenuates Endothelial Dysfunction and Albuminuria in a Chronic Kidney Disease Model by a Reduction in Oxidative Stress - Raquel González-Blázquez; Beatriz Somoza; Marta Gil-Ortega; Miriam Martín Ramos; David Ramiro-Cortijo; Elena Vega-Martín; Angela Schulz; Luis Miguel Ruilope; Luis Miguel Ruilope; Peter Kolkhof; Reinhold Kreutz; María S. Fernández-Alfonso (Frontiers Media S.A., 2018)
Albuminuria is an early marker of renovascular damage associated to an increase in oxidative stress. The Munich Wistar Frömter (MWF) rat is a model of chronic kidney disease (CKD), which exhibits endothelial dysfunction associated to low nitric oxide availability. We hypothesize that the new highly selective, non-steroidal mineralocorticoid receptor (MR) antagonist, finerenone, reverses both endothelial dysfunction and microalbuminuria. Twelve-week-old MWF (MWF-C; MWF-FIN) and aged-matched normoalbuminuric Wistar (W-C; W-FIN) rats were treated with finerenone (FIN, 10 mg/kg/day p.o.) or vehicle (C) for 4-week. Systolic blood pressure (SBP) and albuminuria were determined the last day of treatment. Finerenone lowered albuminuria by >40% and significantly reduced SBP in MWF. Aortic rings of MWF-C showed higher contractions to either noradrenaline (NA) or angiotensin II (Ang II), and lower relaxation to acetylcholine (Ach) than W-C rings. These alterations were reversed by finerenone to W-C control levels due to an upregulation in phosphorylated Akt and eNOS, and an increase in NO availability. Apocynin and 3-amino-1,2,4-triazole significantly reduced contractions to NA or Ang II in MWF-C, but not in MWF-FIN rings. Accordingly, a significant increase of Mn-superoxide dismutase (SOD) and Cu/Zn-SOD protein levels were observed in rings of MWF-FIN, without differences in p22phox, p47phox or catalase levels. Total SOD activity was increased in kidneys from MWF-FIN rats. In conclusion, finerenone improves endothelial dysfunction through an enhancement in NO bioavailability and a decrease in superoxide anion levels due to an upregulation in SOD activity. This is associated with an increase in renal SOD activity and a reduction of albuminuria.